Weaving a 2D net of hydrogen and halogen bonds: cocrystal of a pyrazolium bromide with tetrafluorodiiodobenzene. Issue 6 (9th May 2022) - van Terwingen, Steven; Ebel, Ben; Wang, Ruimin; Englert, Ulli
Abstract : In the cocrystal of the hydrobromide of a substituted pyrazole with tetrafluorodiidobenzene, the bromide anion engages in both hydrogen and halogen bonds. Abstract : Hydrohalides of Lewis bases may act as halogen bond (XB) acceptors and combine two directional interactions, namely, hydrogen bonds (HB) and XBs in the same solid. 3‐(1, 3, 5‐Trimethyl‐1 H ‐pyrazol‐4‐yl)acetylacetone (C11 H16 N2 O2, HacacMePz) was protonated with H X ( X  = Cl or Br) to afford the hydrohalides, C11 H17 N2 O2 + · X − or H2 acacMePz + · X − (1, X  = Cl; 2, X  = Br). Hydrohalides 1 and 2 are isomorphous and adopt a classical dipole packing. Consistent with the observation for most β‐diketones, the enol form with an intramolecular HB is observed. Additional noteworthy interactions are HBs of the protonated pyrazolium towards the X − anion at donor–acceptor distances of 2.9671 (17) Å for 1 and 3.159 (4) Å for 2 . Cocrystallization of hydrobromide 2 with the XB donor tetrafluorodiiodobenzene (TFDIB) leads to the adduct C11 H17 N2 O2 + ·Br − ·0.5C6 F4 I2 ·H2 O or (H2 acacMePz + ·Br − )2 ·(H2 O)2 ·TFDIB (3 ), in which the XB donor TFDIB is situated on a crystallographic centre of inversion. Classical HBs link organic cations, water molecules and Br − anions into chains along [010]. Almost orthogonal to this interaction, XBs with Br…I = 3.2956 (4) Å connect neighbouring chains along [102] into two‐dimensional sheets in the (10 ) plane. Assisted by their negative charge, halide anions represent particularly good nucleophiles towards XB donors.